STOCK ESTIMATE OF SKIPJACK TUNA (Katsuwonus pelamis) CATCHES IN SOUTHERN WATERS OF LATUHALAT, MALUKU, INDONESIA - Imanuel V.T. Soukotta; Domey L. Moniharapon; Wildan Tino; J.A.N. Masrikat (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
Distribution of skipjack tuna (Katsuwonus pelamis) stock, an economically important commodity, has led to a decline in fish size status. Exploitation in the southern waters of Latuhalat village is carried out by various fishing gear, affecting trip and catch production. The study aimed to analyze size distribution, growth pattern, mortality, and sex ratio using Microsoft Excel and FiSAT II software. The results showed a growth coefficient (K) of 0.61 per year and asymptotic length (L∞) of 62.50 cmFL, with a maximum age (t) of 8 years and age at zero length (t0) of -0.23 years. The von Bertalanffy growth equation was Lt = 62.50(1-e^(-0.61(t+0.23))). The cohort pattern consisted of 4 cohorts, with juvenile fish at 23.3 cm and adult fish at 55.5 cm. The fishing mortality rate (F) was 0.03 per year, calculated by subtracting natural mortality rate (M) of 1.07 per year from total mortality rate (Z) of 1.10 per year. The exploitation rate (E) was calculated as E=F/Z, which was 0.03. The sex ratio was 1:1, indicating a balanced population. Recommendation: reduce the catch of adult fish during the third gonad stage to maintain population balance. Key words: Katsuwonus pelamis, Latuhalat waters, population parameters